The feasibility and challenges of energy self-sufficient wastewater treatment plants. (15th October 2017) - Gu, Yifan; Li, Yue; Li, Xuyao; Luo, Pengzhou; Wang, Hongtao; Robinson, Zoe P.; Wang, Xin; Wu, Jiang; Li, Fengting
Highlights: Various influencing factors of energy use in WWTPs are characterized. Benchmark energy consumption in WWTPs in different countries are highlighted. Energy recovery or saving technologies in WWTPs are summarized. Recent advances in optimization of energy recovery technologies are highlighted. Feasibility and challenges of energy self-sufficient WWTPs are explored. Abstract: Energy efficiency optimization is crucial for wastewater treatment plants (WWTPs) because of increasing energy costs and concerns about global climate change. Energy efficiency optimization can be achieved through a combination of energy recovery from the wastewater treatment process and energy saving-related technologies. Through these two approaches energy self-sufficiency of WWTPs is achievable, and research is underway to reduce operation costs and energy consumption and to achieve carbon neutrality. In this paper, we analyze energy consumption and recovery in WWTPs and characterize the factors that influence energy use in WWTPs, including treatment techniques, treatment capacities, and regional differences. Recent advances in the optimization of energy recovery technologies and theoretical analysis models for the analysis of different technological solutions are presented. Despite some challenges in implementation, such as technological barriers and high investment costs, particularly in developing countries, this paper highlights the potential for more energy self-sufficient WWTPs to be established in the future.